IMPLEMENTASI ALGORITMA DATA MINING NAIVE BAYES PADA KOPERASI - Emerensye S. Y. Pandie (Universitas Nusa Cendana, 2018)
One of the factors of failure in the field of credit business is the lack of accurate assessment of the ability of the debtor, thus resulting in errors in credit decisions that culminate in credit congestion. Data mining techniques can be used to assess customer ability based on past data. Debtor data that has been through the stages of data mining is then processed using Naive Bayes data mining algorithm. Naive Bayes is a simple probabilistic based prediction technique based on the application of bayes rules. Implementation using Weka 3.8 with a total of 3018 records yields a truth level of 94%.